Nick and Tesla's high-voltage danger lab : a mystery with electromagnets, burglar alarms, and other gadgets you can build yourself - Pflugfelder, Bob, 1967-; Hockensmith, Steve (Quirk Books, 2013)
After moving in with their eccentric uncle, Nick and Tesla encounter strange occurrences in their new neighborhood and build gadgets using simple household objects to help them solve the mysteries.